Kesan pengedopan berkepekatan rendah ke atas bahan berstructur Nano ZnO:A1 sebagai lapisan anti-pantulan - Huda Abdullah,; Nor Habibi Saadah,; Nugroho Ariyanto,; Muhamad Mad Salleh, (Universiti Kebangsaan Malaysia, 2009)
The effects of substituting low concentration Al at Zn-site as an anti-reflecting coating (ARC) for Zn1-xAlxO compound on structural, morphological and optical properties have been studied. Zn1-xAlxO sample with x = 0.00, 0.05, 0.10 and 0.15 were synthesized via a sol gel method. The films obtained from the sol gel have been annealed at 400°C for 2 hours. X-ray diffraction Method (XIR) and Scanning Electron Microscope (SEM) have been used for structural characterization and morphology of the film. XRD spectra show all samples exhibit hexagonal structure. The particle size decreases with increasing Al concentration. These films exhibit a dense and compact film structure that could be effective for light trapping in thin film solar cells. The optical property has been characterised using UV-Visible-NIR and photoluminescence spectrometer. The band gaps increase as the concentration of Al increases. The increase of the band gap is an important requirement for good anti-reflecting coating element. Therefore these films can be applied as anti-reflecting coating thin film for solar cells.